PENTINGNYA RED FLAG BAGI AUDITOR INDEPENDEN UNTUK MENDETEKSI KECURANGAN DALAM LAPORAN KEUANGAN - NOVIAN TEDJASUKMA, FANNY (Berkala Ilmiah Mahasiswa Akuntansi)
Current the internal and external company already has a consciousness of high in the importance of financial report of a corporation. They realized that financial statement is one of information most could describe whole of the state of the company during this to be able to detect errors cheating or food that occur. Therefore auditor who performs auditing must have the ability to recognize signal (red flags) fraud and error. And the use of standard examination is required by the auditor when conducting an assessment, not only do they set their guidelines on signs, but look at the facts specifically which factor is more important and should be considered, then the auditor can estimate the risk of an audit that occurs within their audit assignments with more consistent and effective